Obstáculos à burocratiza éao de uma vila no sertão paulista, sculo XIX - Fernandes, Edson [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2015)
This work addresses the obstacles to bureaucratization and institutionalization of the judicial, administrative, religious and political-electoral order in a small country town in the second half of the 19th century in the Brazilian state of São Paulo. The area, located between the Tietê and Paranapanema rivers, had been considered for decades the frontier of the settlements. Very little was known about those sertões (the hinterland) except for some descriptive literature that indicated the presence of indigenous people and the constant appeals from local authorities to the provincial government. The obstacles to bureaucratization of institutions did not come from the elites exclusively and, by way of contamination or patronage, reached the lower social classes unwilling to adopt regulating measures issued by local authorities.
Obstacles to bureaucratization in a small paulista country town in the 19th century
Keywords: Bureaucratization; Frontier; Hinterland